Integration of Reading and Writing Literacy in Islamic Education Learning to Develop Student Competencies - Kholili, Moh. Azharul; Mu'id, Abdul (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2025)
The changing times require the education system to not only focus on academic aspects, but also the development of 21st century skills. One strategic approach is the integration of reading and writing literacy in Islamic Religious Education (PAI) learning. This study aims to examine how the integration of literacy in Islamic Education learning can shape students' competencies, especially critical thinking, creativity, communication, and collaboration skills. This research used a qualitative approach with a case study at MTs Al-Khoiriyah 2 Gresik. Data were obtained through in-depth interviews, observation, and documentation. The results show that literacy practices in PAI have involved reading religious texts, writing reflections, and collaborative projects. However, there are still challenges such as limited learning time and contextualized reading materials. This study contributes to the development of literacy-based learning strategies that are transformative and relevant to the needs of the 21st century, and emphasizes the need to strengthen the role of teachers and restructure the curriculum to make PAI learning more meaningful.